Ответы и объяснения

2014-04-05T13:33:14+00:00
  -sina+ cos^{2}a+sin ^{2}a-2cos ^{2}a/sina-cosa=sina* cosa/sina   -sina+[tex]sin ^{2}a-cos ^{2}a  /sina-cosa=cosa
  -sina+(sina-cosa)(sina+cosa)/(sina-cosa)=cosa
  -sina+sina+cosa=cosa 
  cosa=cosa
-sina+[tex] cos^{2}a+sin ^{2}a-2cos ^{2}a/sina-cosa=sina* cosa/sina
-sina+[tex]sin ^{2}a-cos ^{2}a [/tex]/sina-cosa=cosa
-sina+(sina-cosa)(sina+cosa)/(sina-cosa)=cosa
-sina+sina+cosa=cosa
cosa=cosa
-sina+ cos^{2}a+sin ^{2}a-2cos ^{2}a/sina-cosa=sina* cosa/sina
-sina+sin ^{2}a-cos ^{2}a /sina-cosa=cosa
-sina+(sina-cosa)(sina+cosa)/(sina-cosa)=cosa
-sina+sina+cosa=cosa
cosa=cosa